BUILDING PARTNERSHIP ACROSS RURAL TOURISM DESTINATION FOR SUSTAINABILITY: A CASE STUDY IN SPECIAL REGION OF YOGYAKARTA, SOME CHALLENGES AND OPPORTUNITIES - Aris Chandra Pradikta (Journal of Business on Hospitality and Tourism, 2016)
Tourism destination in rural areas often face difficulties to sustain its competitiveness dimension. Economic-geography approach extent the discussion of tourism development that integrate spatial and economic as a result of evolutionary pattern on tourism activities in rural areas. However, within proliferation background of rural tourism destinations such as Special Region of Yogyakarta, 112 rural tourism destinations in a region, are considered as highly competitive and threaten of the future rural tourism destinations sustainability. Therefore, moving beyond focus within a single destination is necessary in order to gain new perspective and reconstruct the regional policy development. This paper tries to reveal some challenges and opportunities in building partnerships across rural tourism destinations. Data in this paper is complemented by graduate thesis research and regional survey of rural tourism social mapping in Special Region of Yogyakarta that authors involved in. Research findings indicated that variables such as homogeneity of attractions, similarity of market sharing, and organizational capacity building are among major needed to address. In addition, top-down planning of local government is expected as a breakthrough of current conditions.